Qur’an and splendor of Islamic calligraphy: development of Iranian calligraphy under influence of Qur’an transcribing / Mahdi Sahragard - Mahdi Sahragard (2015)
It is safe to claim that the emergence of calligraphy as one of the most important art in the Islamic era had a direct relationship with the outmost importance of Qur’an for Muslims. In this line, there are numerous quotations from the Holy Prophet and the Imams about the crucial importance of beautiful transcribing of Qur’an. Therefore, calligraphy quickly spread throughout the world of Islam and developed by artists in different regions. Iranian artists played a significant role in developing of Islamic calligraphy amongst were Ahval-e Moharrar, Ibrāhim sejzi, Ibn-e moqlah-the rule-governor of six scripts- Ibn-e bavvab, and etc. Additionally, a large number of survived manuscripts of Qur’an produced in Iran demonstrate the developing of calligraphy in relation with Qur’an. In this article we reviewed the evolution of the Qur’anic scripts in Iran up to the end of Qajar period (14th / 19th century) and discussed about the importance of Qur’an in developing of Iranian calligraphy.